Molecular basis of preferential resistance to colchicine in multidrug-resistant human cells conferred by Gly-185----Val-185 substitution in P-glycoprotein. - Safa, A R (1990)
Expression of P-glycoprotein, encoded by the human MDR1 gene, results in cross-resistance to many lipophilic cytotoxic drugs (multidrug resistance). P-glycoprotein is believed to function as an energy-dependent efflux pump that is responsible for decreased drug accumulation in multidrug-resistant cells. Previous work showed that preferential resistance to colchicine in a colchicine-selected multidrug-resistant cell line was caused by spontaneous mutations in the MDR1 gene that resulted in a Gly-185----Val-185 substitution in P-glycoprotein. We have now compared transfectant cell lines expressing either the wild-type Gly-185 or the mutant Val-185 P-glycoprotein with regard to their levels of resistance to and accumulation and binding of different drugs. In cells expressing the mutant protein, increased resistance to colchicine and decreased resistance to vinblastine correlated with a decreased accumulation of colchicine and increased accumulation of vinblastine. Expression of the mutant P-glycoprotein also resulted in significantly increased resistance to epipodophyllotoxin and decreased resistance to vincristine and actinomycin D; smaller changes in resistance were observed for several other drugs. Unexpectedly, the mutant P-glycoprotein showed increased binding of photoactive analogs of vinblastine and verapamil and the photoactive compound azidopine and decreased binding of a photoactive colchicine analog. These results suggest that the Gly-185----Val-185 substitution affects not the initial drug-binding site of P-glycoprotein but another site, associated with the release of P-glycoprotein-bound drugs to the outside of the cell.